Scrutinizing the rigorousness of government interventions in addressing homelessness in Malaysia / Noor Amira Syazwani Abd Rahman...[et. al.] - Abd Rahman, Noor Amira Syazwani; Ridzuan, Mohd Rozaimy; Manas, Nur Hidayahtul Nabihah; Wan Mohamad, Wan Sumayyah Syahidah (Universiti Teknologi MARA Cawangan Pahang, 2019)
Homelessness remains a world problem, although a majority of homeless groups survive only in modernized cultures. The occurrence of homelessness is becoming a social problem in Malaysia, especially in city areas such as Kuala Lumpur, Penang and Johor Baharu. It is believed that this group of people has less received much concentration since the current social policies have no direct bearing to the homeless. Hence, this paper analyzes the rigorousness of government interventions in addressing the homelessness in Malaysia. This paper reviews relevant literatures pertaining to programs carried out by the government in helping homeless via preliminary reports, observation and interviews that have been written in previous research. It is hoped that the study will grant to the existing body of knowledge related to homelessness study.